Dengue Hemorrhagic Fever Incidence in Indonesia Using Trend Analysis and Spatial Visualization - Helmy Gani; Rizky Maharja; Hamdan Gani; Nurilmiyanti Wardhani; Nurani Nurani; Nur Fadhilah Gani; Muhammad Akbar Salcha; Riadnin Maharja (International Journal of Public Health Science (IJPHS), 2022)
Dengue hemorrhagic fever (DHF) has caused a public health risk in many developing countries, so understanding their incidence trend is needed to prepare an early warning prevention.The multi-year DHF trend analyses are necessary but have not been accomplished to this day in Indonesia. This study examined time trends using yearly data on the incidences of DHF for all provinces. Univariate forecasting model constructed on the data up to 2019 predicted the future trends in the disease's incidences up to 2022. At the same time, a trend analysis test was developed to explain the disease trend for all regions. The results per province showed a declining trend of DHF cases and TDC in Java Island (i.e., Jawa Barat, Jawa Tengah, DKI Jakarta, and Banten). Then, there was an increasing trend in the majority of regions outside of Java Island. For the CFR and IR, most provinces had decreasing trend except for Gorontalo, Kalimantan Utara, and Maluku. Overall, trend analysis showed a continually decreasing trend of DHF, TDC, CFR, and IR incidence over the past 16 years in Indonesia. The findings highlight the need for preventive policies for several provinces with the increasing trend of DHF incidences.